Kakovost in vrednost okroglega lesa bukve (Fagus sylvatica L.) s posebnim ozirom na pojav rdečega srca - Kadunc, Aleš (Gozdarski vestnik, 2006)
The aim of the paper is to establish the relations between the quality of European beech (Fagus sylvatica L.) trees or stands and tree traits, site characteristics and the influences of silvicultural measures. Red heartwood formation and its impact on timber value are in the focus of the research. Altogether 5058 beech trees on 27 locations and on 13 site units were includedin the research. Each tree was classified into timber quality classes,on all log-fronts the extent of red heartwood was measured. In the analysis six scenarios of timber price lists and three scenarios of harvestingcosts were taken into consideration. With the use of thinnings of adequate intensity in the mature phase of the stands the probability of red heartwood formation and its extent are substantially lower. If our goal is maximum sliced veneer production, then trees of highest timber quality should be harvested when their dbh is between 45 and 50 cm. The result of thinnings are higher shares of sliced veneer timber and sawlog timber of first and second class in comparison with unthinned stands. Different timber price listsscenarios and different harvesting costs scenarios have a rather weak influence on the time of mean annual value stand increment culmination. By contrast the production period is strongly influenced by the age of trees or stands. On less productive sites there is a very wide time range when it is possible to utilize the mean annual value increment of the stands, while on more productive sites, particularly on limestone bedrock, delaying culminationof mean annual value increment of the stands relatively quickly leads to financial losses.
Keywords: bukev; Fagus sylvatica L.; sestoji; prirastek; les; kvaliteta; rdeče srce